2019
DOI: 10.1172/jci121987
|View full text |Cite
|
Sign up to set email alerts
|

PTEN-induced partial epithelial-mesenchymal transition drives diabetic kidney disease

Abstract: Epithelial-mesenchymal transition (EMT) contributes significantly to interstitial matrix deposition in diabetic kidney disease (DKD). However, detection of EMT in kidney tissue is impracticable, and anti-EMT therapies have long been hindered. We reported that phosphatase and tensin homolog (PTEN) promoted transforming growth factor beta 1 (TGF-β), sonic hedgehog (SHH), connective tissue growth factor (CTGF), interleukin 6 (IL-6), and hyperglycemia-induced EMT when PTEN was modified by a MEX3C-catalyzed K27-lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 58 publications
2
54
0
Order By: Relevance
“…We observed that mechanical or chemical stimulation upregulated YAP induced IL‐6 production in bEECs and had no obvious effect on other inflammatory factors (Figure 5E, Figure B), which are proposed to be essential for the formation of the maternal uterine immune environment during the preimplantation period. We also found that IL‐6 positively regulates YAP activation in bEEc cells (Figure 5F), consistent with previous studies in an organ injury model 35,36 . The expression of the uterine receptive markers LIF and VEGF also exhibited a positive correlation with YAP (Figure 5G).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…We observed that mechanical or chemical stimulation upregulated YAP induced IL‐6 production in bEECs and had no obvious effect on other inflammatory factors (Figure 5E, Figure B), which are proposed to be essential for the formation of the maternal uterine immune environment during the preimplantation period. We also found that IL‐6 positively regulates YAP activation in bEEc cells (Figure 5F), consistent with previous studies in an organ injury model 35,36 . The expression of the uterine receptive markers LIF and VEGF also exhibited a positive correlation with YAP (Figure 5G).…”
Section: Resultssupporting
confidence: 91%
“…We also found that IL-6 positively regulates YAP activation in bEEc cells ( Figure 5F), consistent with previous studies in an organ injury model. 35,36 The expression of the uterine receptive markers LIF and VEGF also exhibited a positive correlation with YAP ( Figure 5G). These results indicate that YAP activation provides the conditions required for early pregnancy.…”
Section: F I G U R Ementioning
confidence: 82%
“…identified the small molecule triptolide as an inhibitor of the enzymatic activity of MEX3C, out of 2027 bioactive compounds screened. This natural compound targeted the UBE2S‐MEX3C interaction leading to inhibition of epithelial‐mesenchymal transition in renal epithelial cells (Li et al., 2019).…”
Section: Mex3cmentioning
confidence: 99%
“…Folic acid-induced renal hypertrophy was first observed in rats in the 1960s, though it has never been reported in humans [76,77,78]. Ever since, the mechanisms underlying folic acid-induced kidney injury have been investigated, partially characterized, and, to this day, considered a valuable animal model to study acute kidney injury onset, progression, and possible protective strategies [78,79,80,81,82].…”
Section: Folic Acid-induced Acute Kidney Injury Modelmentioning
confidence: 99%